2000
DOI: 10.1093/emboj/19.4.776
|View full text |Cite
|
Sign up to set email alerts
|

Tn10 transpososome assembly involves a folded intermediate that must be unfolded for target capture and strand transfer

Abstract: Tn10 transposition, like all transposition reactions examined thus far, involves assembly of a stable protein-DNA transpososome, containing a pair of transposon ends, within which all chemical events occur. We report here that stable Tn10 pre-cleavage transpososomes occur in two conformations: a folded form which contains the DNA-bending factor IHF and an unfolded form which lacks IHF. Functional analysis shows that both forms undergo double strand cleavage at the transposon ends but that only the unfolded for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 29 publications
3
43
0
Order By: Relevance
“…5B). This experiment demonstrates that occupancy of IHF sites is low in this transpososome, which is indicative of an unfolded transpososome (Sakai et al 2000;Crellin and Chalmers 2001). With this substrate IHF binding is revealed by hypersensitivity to OP-Cu at nucleotides 27 and 28, and by OP-Cu protection in the region of nucleotides 31-45 on the transferred strand (Fig.…”
Section: H-ns Binding To the Terminal Inverted Repeat Stabilizes Tranmentioning
confidence: 71%
See 2 more Smart Citations
“…5B). This experiment demonstrates that occupancy of IHF sites is low in this transpososome, which is indicative of an unfolded transpososome (Sakai et al 2000;Crellin and Chalmers 2001). With this substrate IHF binding is revealed by hypersensitivity to OP-Cu at nucleotides 27 and 28, and by OP-Cu protection in the region of nucleotides 31-45 on the transferred strand (Fig.…”
Section: H-ns Binding To the Terminal Inverted Repeat Stabilizes Tranmentioning
confidence: 71%
“…We have seen no evidence of this in footprinting studies (data not shown). Moreover, since we know that the conformation of the OE substrate is a major determinant of transpososome mobility (Sakai et al 2000), we favor the idea that comigration of H-NS-bound forms of folded and unfolded transpososomes reflects H-NSdirected transpososome unfolding.…”
Section: H-ns and Transpososome Unfoldingmentioning
confidence: 82%
See 1 more Smart Citation
“…An alternative mechanism would be that direct interaction between IHF and transposase produces a conformational change in transposase that precludes target interactions. Limited support for a direct protein±protein interaction is provided by the observation that IHF has a higher af®nity for the IHF binding site in the Tn10 transpososome than for the free transposon end (19).…”
Section: Molecular Models Of the Tn10 Transpososomementioning
confidence: 99%
“…From the molecular model in Figure 1A, it is easy to visualize why Tn10 transposase would require a contribution from the energy of IHF binding or negative supercoiling to bend the DNA and establish the subterminal contacts. These contacts are required to activate the chemical steps during the cleavage reaction and must be disengaged to allow target interactions later in the reaction (18,19). In this paper, we investigate the symmetry of the IHF-folded arms of the transposon during transpososome assembly, and the properties of the conformational change leading to disengagement of the subterminal contacts and ejection of IHF from the complex.…”
Section: Introductionmentioning
confidence: 99%